2018
DOI: 10.1093/glycob/cwy007
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression, characterization and possible functions of the chitin deacetylases, Cda1 and Cda2, from mushroom Coprinopsis cinerea

Abstract: Two chitin deacetylases, Cda1 and Cda2, from Coprinopsis cinerea were expressed and characterized. Cda1 preferably deacetylates the nonreducing end residue of (GlcNAc)2, the internal or nonreducing end residue of (GlcNAc)3 and the nonreducing residue of (GlcNAc)6 after deacetylating the internal residues. In contrast, Cda2 preferably deacetylates the reducing end residue of (GlcNAc)2, the internal or reducing end residue of (GlcNAc)3 and the reducing residue of (GlcNAc)6 after deacetylating the internal residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In this work the effects of wheat bran feruloyl oligo-Compared to the control group, the serum catalase (CAT), glutathione peroxidase (GSH- [78] saeeharides (FEOS), as an antioxidant supplement Px) and superoxide dismutase (SOD) activities and glutathione (GSH) levels of lambs for perform-ance, were investigated with respect to were sigoificantly higher, while the serum total antioxidant capacity (T -AOC) slightly blood metabolite levelll, antioxidant status and rumiincreased. nal fermentation in lambs.…”
Section: Feruloyl Oligo1aeebaride1 (Feos) and Otbenmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work the effects of wheat bran feruloyl oligo-Compared to the control group, the serum catalase (CAT), glutathione peroxidase (GSH- [78] saeeharides (FEOS), as an antioxidant supplement Px) and superoxide dismutase (SOD) activities and glutathione (GSH) levels of lambs for perform-ance, were investigated with respect to were sigoificantly higher, while the serum total antioxidant capacity (T -AOC) slightly blood metabolite levelll, antioxidant status and rumiincreased. nal fermentation in lambs.…”
Section: Feruloyl Oligo1aeebaride1 (Feos) and Otbenmentioning
confidence: 99%
“…Although widely used, NMR has low sensitivity and severe signal overlap, which often makes data interpretation difficult [71]. [77] and products of the action of chitin deacetylases (Cdal and Cda2) from 1he mushroom Coprinopsis cinerea on chitin oligosaccharides [78].…”
Section: Q11antification and Str11ctllralanalysis Ofoligosaccharilksmentioning
confidence: 99%
See 1 more Smart Citation
“…to construct the main structure of fungal cell wall, significantly contributing to its integrity (Wang et al, 2018b). The partial deacetylation of chitin by chitin deacetylases is usually considered to confer chitin resistance to hydrolysis by chitinases for selfdefense and ability for coping with stress (Christodoulidou et al, 1996).…”
Section: A Potential Disease Mechanismmentioning
confidence: 99%
“…Numerous studies have reported the preparation and biomedical properties of modied chitosan such as gra-copolymerization, alkylation or multiple alkylation, carboxymethylation, michael addition and direct conjugation to chemotherapeutics as well as peptides or proteins. [24][25][26][27][28][29][30][31][32][33][34] Chitosan derivatives, N-quaternization modied chitosan, i.e. N,N,N-trimethyl chitosan (TMC) achieves considerable attention as a drug and gene carrier because of its physiochemical stability, biocompatibility, synthetic feasibility and controllable cationic charge as well as its water-solubility via regulation of its hydrophilic and hydrophobic groups.…”
Section: Introductionmentioning
confidence: 99%